DOES RELIGIOSITY MATTER IN THE ERA OF INDUSTRIAL REVOLUTION 4.0? - Ahmad Amri Zainal Adnan; Nek Kamal Yeop Yunus; Arsalan Mujahid Ghouri (Asian Academy of Management Journal, 2019)
Since the hype of Industrial Revolution 4.0 that was brought up by Klaus Schwab in 2016, once again the question of values and beliefs becomes a debate. If religiosity is sidelined in our efforts to automate services and let machines do the jobs of human, then human will truly be substituted by artificial intelligence (AI). Does religiosity matter and can it play a role in the new industry revolution? This study will explore the impact of religiosity towards Muslim officers’ work behaviour in the higher learning institutions in Malaysia. Through in-depth interviews and thematic analysis, this study found that religiosity has an impact on the respondents’ work behaviour to a certain degree. Five themes emerged from the thematic analysis: religiosity, personality, competency, environment, and leadership. Besides religiosity, factors such as attitude, leadership, and environment also play a vital role in the enhancement of a religious-based organisational culture.